THE INFLUENCE OF AUDITOR INDEPENDENCE, EXPERIENCE, PROFESSIONAL SKEPTICISM, COMPETENCE AND TIME PRESSURE ON AUDITOR ABILITY TO DETECT FRAUD : Study at the Kampar Regency Inspectorate - Gustini, Lidia; Sosiady, Mulia; Ermansyah, Ermansyah (LPPM STMIK Dharmapala Riau, 2025)
Fraud is an unlawful act committed by individuals, either from within or outside an organization, with the intention of gaining personal or group benefits while causing harm to others. This study aims to analyze the influence of independence, experience, professional skepticism, competence, and time pressure on auditors' ability to detect fraud. The object of this research is auditors working at the Inspectorate of Kampar Regency, with a sample size of 42 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 30.The results show that independence, experience, competence, and time pressure have a significant influence on auditors’ ability to detect fraud. In contrast, professional skepticism does not have a significant influence. Simultaneously, all five independent variables significantly affect the auditors’ ability to detect fraud within the Inspectorate of Kampar Regency.